European Thyroid Association Guidelines for Ultrasound Malignancy Risk Stratification of Thyroid Nodules in Adults: The EU-TIRADS. Issue 5 (8th September 2017) - Russ, Gilles; Bonnema, Steen J.; Erdogan, Murat Faik; Durante, Cosimo; Ngu, Rose; Leenhardt, Laurence
Abstract : Thyroid ultrasound (US) is a key examination for the management of thyroid nodules. Thyroid US is easily accessible, noninvasive, and cost-effective, and is a mandatory step in the workup of thyroid nodules. The main disadvantage of the method is that it is operator dependent. Thyroid US assessment of the risk of malignancy is crucial in patients with nodules, in order to select those who should have a fine needle aspiration (FNA) biopsy performed. Due to the pivotal role of thyroid US in the management of patients with nodules, the European Thyroid Association convened a panel of international experts to set up European guidelines on US risk stratification of thyroid nodules. Based on a review of the literature and on the American Association of Clinical Endocrinologists, American Thyroid Association, and Korean guidelines, the panel created the novel European Thyroid Imaging and Reporting Data System, called EU-TIRADS. This comprises a thyroid US lexicon; a standardized report; definitions of benign and low-, intermediate-, and high-risk nodules, with the estimated risks of malignancy in each category; and indications for FNA. Illustrated by numerous US images, the EU-TIRADS aims to serve physicians in their clinical practice, to enhance the interobserver reproducibility of descriptions, and to simplify communication of the results.